1972
DOI: 10.1128/jb.112.3.1254-1263.1972
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Tyrosine Biosynthetic Enzymes in Salmonella typhimurium : Analysis of the Involvement of Tyrosyl-Transfer Ribonucleic Acid and Tyrosyl-Transfer Ribonucleic Acid Synthetase

Abstract: Mutants of Salmonella typhimurium were isolated that require tyrosine for growth because of an altered tyrosyl-transfer ribonucleic acid (tRNA) synthetase. Extracts of one strain (JK10) contain a labile enzyme with decreased ability to transfer tyrosine to tRNA Tyr and a higher K m for tyrosine than the wild-type enzyme. Strain JK10 maintains repressed levels of the tyrosine biosynthetic enzymes when the growth rate is restrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

1973
1973
1980
1980

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Camarakis and Pittard (6) found that when the trpSand trpRalleles were present in the same cell the specific activity of AS in a culture grown in nutrient broth was 12-fold higher than that of trpS+ trpRstrains. This combined regulatory effect was also noted by Heinonen et al (14) for tyrS strains that were not derepressed when grown at restrictive temperatures. It should be noted, however, that the equivalence of the B. subtilis mtr locus and the E. coli trpR and tyrR regulatory genes has not been established.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Camarakis and Pittard (6) found that when the trpSand trpRalleles were present in the same cell the specific activity of AS in a culture grown in nutrient broth was 12-fold higher than that of trpS+ trpRstrains. This combined regulatory effect was also noted by Heinonen et al (14) for tyrS strains that were not derepressed when grown at restrictive temperatures. It should be noted, however, that the equivalence of the B. subtilis mtr locus and the E. coli trpR and tyrR regulatory genes has not been established.…”
Section: Discussionsupporting
confidence: 78%
“…Eidlic and Neidhardt (9) and Roth and Ames (34) demonstrated that mutants of Escherichia coli and Salmonella typhimurium possessing an inactive synthetase or one having decreased affinity for histidineor valine-accepting tRNA (tRNAvaI) exhibited marked derepression of the histidine or valine biosynthetic enzymes, respectively. The tryptophan biosynthetic enzymes are derepressed in tryptophanyl-tRNA synthetase (TRS) mutants of E. coli (19,20), and the synthetases have also been implicated as controlling elements of the biosynthesis of branched-chain amino acids (1,5,23) and tyrosine (14). Similar modes of control have been observed in eukaryotic organisms for an isoleucyl-tRNA synthetase mutant of Saccharomyces (26) and a TRS mutant of Neurospora (30).…”
mentioning
confidence: 73%
“…That tyrosine rather than charged tRNATYr is the corepressor in tyrosine regulation in E. coli seems likely from the work of Ravel et al (24), which demonstrated that certain analogues which were not activated by tyrosyl-tRNA synthetase were, nevertheless, able to repress the synthesis of DAHP synthetase (tyr). Heinonen et al (11), in a more extensive study of the regulation of DAHP synthetase (tyr) in S. typhimurium, showed that charging of tRNATYr seems to be unnecessary for repression. This conclusion was based on the repressed levels of tyrosine biosynthetic enzymes in a tyrS mutant when the growth rate was restricted by limitation of charged tRNATYr and, in addition, the ability of analogues that are not activated to mediate repression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the regulation of amino acid biosynthesis in Escherichia coli and Salmonella typhimurium have indicated that there are several different mechanisms by which amino acids regulate the synthesis of the enzymes in their respective biosynthetic pathways (7,25). In the histidine and branchedchain amino acid pathways, the aminoacyltransfer ribonucleic acids (tRNA's) have been implicated as corepressors (5,13,26), whereas in the aromatic amino acid pathway, the evidence has indicated that the free amino acids function as corepressors (12,14,19,20,23). hisT mutants of S. typhimurium are of particular interest because they contain normal levels of the aminoacyl-tRNA's, and yet the enzymes of the histidine and isoleucine-valine pathways are derepressed (6,8,10,21).…”
mentioning
confidence: 99%
“…0-succinylhomoserine synthetase, a biosynthetic enzyme specific for the methionine pathway, is repressed to the same extent by methionine in the hisT mutant as in wild type. It is of interest to note that the levels of the determined by the procedure of Heinonen et al (14). Reaction mixtures contained 5 to 50 jug of cell extract protein and were incubated for 10 min at 370C.…”
mentioning
confidence: 99%